Changing lanes [videorecording (DVD)] - Michell, Roger, 1956-; Jackson, Samuel L.; Affleck, Ben, 1972-; Collette, Toni; Pollack, Sydney, 1934-2008; Hurt, William; Peet, Amanda, 1972- (Paramount Pictures, 2002)
A minor traffic accident turns two perfect strangers into vicious adversaries waging an all-out war of personal destruction.